2014
DOI: 10.4236/ojanes.2014.44013
|View full text |Cite
|
Sign up to set email alerts
|

Pain on Injection of Propofol: Efficacy of Paracetamol and Lidocaine

Abstract: Background and Objectives: Propofol remains the most common drug for induction of general anaesthesia, although it causes considerable pain on injection. None of the commonly used methods completely attenuate this discomfort. We aimed to investigate the effect of i.v. paracetamol pretreatment on the propofol injection pain. Materials and Methods: A prospective randomized double-blind study was conducted on 180 patients, ASA I or II status, scheduled to undergo elective surgery. They were randomly assigned to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Canbay et al [15] showed that the incidence of propofol injection pain was 64% in the control group and 22% in the intravenous paracetamol pretreatment group. Khouadja et al [31] also showed similar results, 85% in the control group and 36.6% in the intravenous paracetamol group.…”
Section: Discussionmentioning
confidence: 54%
“…Canbay et al [15] showed that the incidence of propofol injection pain was 64% in the control group and 22% in the intravenous paracetamol pretreatment group. Khouadja et al [31] also showed similar results, 85% in the control group and 36.6% in the intravenous paracetamol group.…”
Section: Discussionmentioning
confidence: 54%
“…Canbay et al [15] showed that the incidence of propofol injection pain was 64% in the control group and 22% in the intravenous paracetamol pretreatment group. Khouadja et al [27] also showed similar results, 85% in the control group and 36.6% in the intravenous paracetamol group.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, the overall incidence of pain during propofol injection was higher than other studies. The previous 3 studies [15,27,28] used intravenous paracetamol, not oral tablet as we did. Oral form of paracetamol exerts different pharmacokinetics and pharmacodynamics in comparison to intravenous form.…”
Section: Discussionmentioning
confidence: 96%
“…Khouadja et al . [31] performed a double-blinded RCT in 180 patients and also showed similar results, 85 % in the control group and 36.6% in the intravenous paracetamol group. Our results revealed that premedication with oral paracetamol reduced the incidence and severity of propofol injection pain.…”
Section: Discussionmentioning
confidence: 61%